Disease-Specific Outcome Analysis of Palliation With the Modified Blalock-Taussig Shunt. (January 2015) - Bove, Thierry; Vandekerckhove, Kristof; Panzer, Joseph; De Groote, Katya; De Wolf, Daniel; François, Katrien
Background: Albeit being a simple surgical procedure, adverse outcomes with the modified Blalock-Taussig shunt (MBTS) are commonly reported in generalizing terms, independent of the underlying heart disorder. Methods: From August 1995 to December 2013, a total of 150 children underwent an MBTS for tetralogy of Fallot (TOF; n = 44, 29%), pulmonary atresia with ventricular septal defect (PA/VSD; n = 28, 19%), pulmonary atresia with intact ventricular septum (PA/IVS; n = 17, 11%), transposition of the great arteries with ventricular septal defect (TGA/VSD) with pulmonary stenosis (PS; n = 12, 8%), Ebstein malformation (n = 2, 1%), and complex univentricular anomalies (n = 47, 31%). Outcome analysis focused on operative mortality and survival until shunt takedown, adjusted to the underlying disease. Results: In-hospital mortality was 8.7% (n = 13), and interstage mortality was 5.1% (n = 7), resulting in 86.1% survival to the next surgery. Hospital mortality was 14% in PA/VSD, 13% in univentricular heart, and 18% in PA/IVS, while no mortality was observed in TOF, TGA/VSD/PS, and Ebstein disease. A shunt-related complication was observed in 18% (n = 27) of the children, including acute thrombosis (n = 7, 5%), shunt stenosis (n = 3, 2%), overshunting (n = 7, 5%), and pulmonary artery stenosis (n = 10, 7%). Multivariate analysis of shunt-dependent time survival identified a shunt complication occurring in a univentricular circulation (hazard ratio [HR] 4.10, 95% confidence interval [CI] = 1.05-17.43, P = .01) and increased shunt size-to-weight ratio (HR 2.72, 95% CI = 0.80-9.18, P = .04) as risk factors. Shunt thrombosis was also a negative outcome predictor in PA/VSD, when requiring associated unifocalization ( P = .05). Conclusion: This study shows that the outcome of palliation with the MBTS is importantly affected by the occurrence of a shunt-related complication, whose circulatory effect is even more dismal in single ventricle hearts. Since an increased shunt size-to-weight ratio additionally compromises the shunt-dependent survival, it emphasizes that the choice of the shunt with regard to size as well as surgical approach remains critical.